Bilateral legacies in East and Southeast Asia - Ganesan, N. (Narayanan) 1958- (ISEAS Publishing, 2015)
This edited volume examines the concept of overhangs or legacies or negative stereotypical images in international relations and their impact on bilateral relations between geographically proximate states in East Asia. The case studies chosen -- Japan-Korea, Japan-China, Vietnam-China, Thailand-Myanmar and Thailand-Cambodia -- demonstrate conclusively that bilateral overhangs or legacies have a significant impact on contemporary international relations. Such images are regularly replicated and stoked by a variety of constituencies, including state agencies, for their own selfish interests. The evidence also points to the fact that such bilateral relationships are relatively self-contained and often operate with their own dynamics. Powerful condensation symbols are appropriated to weave a story of the virtuous self and the stereotypical other. This negative image and its replication is important to an understanding of turbulent bilateral relations in East Asia and also helps to inform how such relations can be brought to an even keel.